Exploring cardiac macrophage heterogeneity in the healthy and diseased myocardium. (February 2021) - Zaman, Rysa; Hamidzada, Homaira; Epelman, Slava
Highlights: Three resident cardiac macrophage subsets of differential origin and lifecycles. Recruited monocytes adopt numerous fates within injured myocardium. Resident/recruited macrophages framework to study distinct functional responses. Analogous macrophage subpopulations are conserved in the human heart. Abstract : Cardiac macrophages maintain homeostasis and orchestrate response to disease. Utilization of genetic fate-mapping and single-cell RNA sequencing shifted the paradigm of macrophage heterogeneity from the canonical M1/M2 classification in favour of a nuanced approach that reconciles divergent origins, lifecycles, and transcriptional states. Here, we provide a conceptual framework to assess cardiac macrophage complexity that integrates transcriptional and functional heterogeneity that tracks with subset-specific markers (TIMD4 and CCR2). Our goal is to provide a starting point for researchers to dissect the functions of known resident cardiac macrophage subpopulations. We discuss recent advances and limitations in our understanding of cardiac macrophage diversity in ischemic injury, hypertension and myocarditis.